Metal-Organic Frameworks as Promising Photosensitizers for Photoelectrochemical Water Splitting - Zhang, Liping (2016)
Ti-based metal-organic frameworks (MOFs) are demonstrated as promising photosensitizers for photoelectrochemical (PEC) water splitting. Photocurrents of TiO2 nano wire photoelectrodes can be improved under visible light through sensitization with aminated Ti-based MOFs. As a host, other sensitizers or catalysts such as Au nanoparticles can be incorporated into the MOF layer thus further improving the PEC water splitting efficiency.